(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
PT.X, a coal mining company in South Kalimantan, Indonesia, plans to use the highwall mining method to excavate marginal reserves on the final slope to maintain production. However, the stability of the slope and determination of the highwall mining dimensions are major concerns due to unfavourable rock mass conditions caused by intensive weathering and tectonics. This paper aims to evaluate the feasibility of highwall mining in the study area using empirical, analytical and numerical methods. The innovation of this research is the integration of these methods, which include rock mass classification, analytical calculation of load and rock support strength, 2D and 3D numerical modelling, and estimation of recovered coal from the highwall design. The initial condition assessment using rock mass classification and analytics calculation of the mining geometry model determined mine openings and pillar dimensions. Numerical modelling re-evaluated the geometry models to obtain an optimal design. The suggested optimal thickness, mine opening, web pillars, and barrier pillars are 3.20, 3.00, 3.50, and 4.00 m, respectively, with four web pillars in one panel at Seam-C and 2.50, 3.00, 3.50, and 4.00 m with four web pillars in one panel at Seam-D. The recovery of coal for Seam-C and Seam-D is estimated to be 40.54%. Deformation was found to have the closest relationship with the dimensions of the mine opening, and the safety factor is most sensitive to changes in the depth of the mine opening. This study provides a reference for future highwall mining in Indonesia and other regions with similar conditions.